The relationship between self-esteem and self-worth protection strategies in university students. (January 2016) - Ferradás, María del Mar; Freire, Carlos; Valle, Antonio; Núñez, José Carlos; Regueiro, Bibiana; Vallejo, Guillermo
Abstract: Self-esteem is one of the variables that are most frequently linked to the adoption of self-protection strategies. However, the nature of this relationship continues to be controversial. The present study examines the relationship between self-esteem and the use of behavioral and claimed self-handicapping, as well as of defensive pessimism, and their relationship with gender in university students. A total of 1031 university students took part in the study. For women, polynomial regression analysis demonstrated a negative linear relationship of claimed self-handicapping and a tendency toward a quadratic relationship in the case of behavioral self-handicapping, as well as a mainly quadratic relationship in the use of defensive pessimism. For men, a negative linear relationship was found in all cases. The theoretical and psychoeducational implications of these findings are discussed. Highlights: Self-esteem and claimed self-handicapping show a negative linear relation for women. A quadratic relationship seems to be in behavioral self-handicapping. A mainly quadratic relationship seems to be in defensive pessimism. For men, a negative linear relationship is found in all cases.